Revisiting Hyman: direct democracy, shop steward organisation and labour process conflict at Ford's Dagenham plant. (1st April 2016) - ,
Abstract : This article utilises detailed research into workplace trade unionism in the Dagenham plant of the Ford Motor Company in the UK to explore fundamental issues of workplace trade union democracy, organisation and struggle. Within this framework, the article re-examines Richard Hyman's influential analysis of workplace trade union representation and 'bureaucratisation'. It draws on a larger study by the author.